Doctrine creation – the stage of the state (power - volitional) management process of social behaviour of the subjects of public relations - Kuznietsov, Serhii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
In this article the process of the state (power-volitional) management of social behaviour of the subjects of public relations was studied. The author of the study assumes that each process consists of several stages that differ in content and mechanisms, but if to talk about the process of managing social behaviour, it should be kept in mind that this process takes place at two levels: level of public (socially conscious) management and level of state (power-volitional) management. Tthe sequence of stages, steps and their content were analyzed as the components of the process of managing social behaviour of the subjects of public relations at the level of the state (power-volitional) management and the determination of the place, role and content of doctrine creation as a stage of this process, in particular legal (maritime) doctrine, which is the result of a process that also consists of a certain sequence of steps. The author’s vision of the content and use of terms that denote certain definitions used in the field of this study was formulated.